ИСКУССТВО КАК ПРОЕКТ СПАСЕНИЯ: к вопросу об эстетике Пастернака (Филолошке студије, 2019)
The article represents an analysis of Boris Pasternak’s poem “Vesna, ty syrost` rudnika v viskah” (1915). The author reveals the latent plan of the text by comparing it to Pasternak’s reflections on art in “Okhrannaya gramota”. Pasternak turns the traditional motive of spring awakening into a new semantic plan – the origin of art. The spring in this poem becomes a metaphor to creative work, which is based on the idea of art’s mission as of salvation, transfiguration of the whole reality. Mythological motives are revealed in the text, a connection between the myth about Hyacinth’s death and Christian sacrifice.